2023
DOI: 10.21203/rs.3.rs-3325715/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of the hyolaryngeal architecture in horseshoe bats: Insights into the evolution of the pulse generation for laryngeal echolocation

Taro Nojiri,
Masaki Takechi,
Toshiko Furutera
et al.

Abstract: Background The hyolaryngeal apparatus generates biosonar pulses in the laryngeally echolocating bats. The cartilage and muscles comprising the hyolarynx of laryngeally echolocating bats are morphologically modified compared to those of non-bat mammals, as represented by the hypertrophied intrinsic laryngeal muscle. Despite its crucial contribution to laryngeal echolocation, how the development of the hyolarynx in bats differs from that of other mammals is poorly documented. The genus Rhinolophus is one of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
(164 reference statements)
1
1
0
Order By: Relevance
“…Bats have also been reported to learn vocalizations, including echolocation frequencies, from their mothers [36]. Furthermore, it has been reported that ultrasonic sound generation at the larynx required least two weeks after birth in bats [37]. Considering these findings, bat larynx muscles may specialize into SFM postnatally facilitated by vocal learning similar to songbirds, although laryngeal anatomical architecture is established prenatally as reported in this study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Bats have also been reported to learn vocalizations, including echolocation frequencies, from their mothers [36]. Furthermore, it has been reported that ultrasonic sound generation at the larynx required least two weeks after birth in bats [37]. Considering these findings, bat larynx muscles may specialize into SFM postnatally facilitated by vocal learning similar to songbirds, although laryngeal anatomical architecture is established prenatally as reported in this study.…”
Section: Discussionsupporting
confidence: 53%
“…In the future, functional morphological analyses should be done to understand the relationship between laryngeal anatomy and acoustic properties of the ultrasonic sounds produced in bats [30]. Moreover, new insights into evolutionary history of the bat laryngeal echolocation should be obtained from observation of innervation pattern of the laryngeal muscles [30,37] and studies of molecular mechanisms that regulate the laryngeal morphogenesis and SFM formation in the echolocating bat lineages.…”
Section: Discussionmentioning
confidence: 99%